Production of laccase by Bacillus subtilis and Aspergillus niger for treatment of textile effluent - Olabisi Peter Abioye; Suleiman Umaru; Sesan Abiodun Aransiola; Oluwafemi Adebayo Oyewole; Naga Raju Maddela; Ram Prasad (Sustainable Chemistry for the Environment, 2025)
The improper disposal of textile effluents without effective treatment has adverse environmental, social, economic, and health impacts and as such, it is vital to find innovative technological solutions to reduce the negative consequences of textile effluents. Laccases are versatile multicopper enzymes found in plants, fungi and other microorganisms with wide applications especially in the textile and paper industry. This study examined the production of laccase from Bacillus subtilis and Aspergillus niger to remediate textile effluent. Both organisms were identified by molecular method and plate test method was used to evaluate laccase production by the two organisms. Rice bran emerged as the substrate of choice for laccase production. At optimum temperature (30°C), the highest laccase produced was 0.522 U/mL and 0.642 U/mL at 35°C for B. subtilis and A. niger respectively. The optimum pH level of 5 and 6 produced the highest laccase yield of 0.583 U/mL and 0.684 U/mL respectively. Significant improvements of laccases from B. subtilis and A. niger were observed on physicochemical analysis of TDS, pH, electrical conductivity, TSS, temperature and DO in treating textile effluent. Notably, these enzymes exhibited remarkable efficacy reduction in BOD (38 %), COD (14 %), and nitrate (23 %) levels in the effluent. The study underscores the efficacy of laccases from the microorganisms in treating textile effluent, with concentrations ranging from 10 to 30 U/mL proving effective. However, laccase produced from B. subtilis showed more remediation potential in textile effluent treatment compared to the one produced by A. niger.